Assessment of afforestation and forest restoration project in District Buner, Khyber Pakhtunkhwa, Pakistan - Ahmad, Khan Ishfaq (2022)
Climate change is one of the biggest issues of this century. Global temperature is continuously increasing and thus affecting the environment. A forest ecosystem is considered one of the most significant ecosystems in combating climate change. As a signatory nation of the Kyoto Protocol, Pakistan is committed to address global warming issues, protecting the existing forest and enhancing the carbon sequestration potential through afforestation, reforestation, and sustainable forest management. To comply with the Bonn Challenge effort, the government of Khyber Pakhtunkhwa, Pakistan, initiated the Billion Tree Afforestation Project (BTAP) which has recently been completed. The major objective of this project was to restore and protect the forest to remove carbon from the atmosphere. Two major methods were followed for forest restoration; enclosure establishment (to promote natural regeneration) and forest plantations. This study investigated the forest restoration sites in District Buner, Khyber Pakhtunkhwa, Pakistan. The study area was divided into two types i.e., enclosures (natural forest) and plantations.15 sites from each forest type (i.e. 15 sites from natural forest and 15 sites from plantations) were selected, covering the whole area for data collection. The data was collected during October, 2020 to December, 2020, following Simple Random Sampling technique. At least 5-12 sample plots of 250 m2 area were laid out in each site to collect data in the field. The survival rate of tree species, , their composition, and their biomass (carbon) in both sites (natural regeneration and plantations) were studied and analyzed. The survival rate of planted seedlings on each plot was then evaluated by counting both live and dead individuals. Through the assessment of survival rate, the success or failure of plantations can be determined. The study revealed that the enclosure (assisted natural regeneration) sites mainly consisted of Pinus roxburghii, while plantation sites mostly comprised broadleaved species. Eucalyptus camaldulensis was the most planted species with about 77.45% of the total species while Pine species (i.e., Pinus roxburghii) proportion was only about 3.19%. The rest of the 19.37% were other broadleaved species. Similarly, the enclosure sites were mainly comprised of Pinus roxburghii with about 54.78%, followed by Dodonaea viscosa with 12.14%. The overall average density of the natural forest was recorded as 1384.17 individuals per ha while the mean density of plantation sites was found to be 1131.6 per ha. The density of new regenerations in natural forest is comparatively high and is not established yet. The average survival rate of all plantation sites was about 58.49%where the highest average survival rate was 82.45%while the lowest survival rate of a site was 37.04%. The carbon sequestration potential of Pinus roxburghii grown in plantations and enclosures was calculated for the year 2050 while using the growth rates (diameter and height) of the species. The growth data were obtained from the Yield Table of the species prepared by the Pakistan Forest Institute. Different allometric equations were applied to estimate the above-ground biomass of the study area. Using each question, the average aboveground carbon stock of Pinus roxburghii in the natural forest was estimated as 9.83 t/ha, 12.67 t/ha, and 12.74 t/ha. The average carbon stock of Pinus roxburghii grown in the plantation was estimated as 1.33 t/ha, 1.72 t/ha, and 1.72 t/ha using each equation. All broadleaved species (such as Eucalyptus camaldulensis, Morus alba, Dalbergia sissoo, Melia azedarach, Cassia fistula) of the plantation sites have the potential to sequester about 0.5 million tons of CO2 until 2030. The restoration campaign in the present study area can be considered successful in terms of wood production, reducing pressure on natural forests and carbon sequestration but it may not be effective in terms of biodiversity and resilience. Hence, increasing the proportion of indigenous multiple tree species is suggested to develop a resilient and diverse ecosystem.